HUKUM ISLAM DAN DINAMIKA FEMINISME DALAM ORGANISASI NAHDLATUL ULAMA’ - Mulia, Musdah (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2013)
The development of the feminist movement has significantly demonstrated in the history of the Nahdlatul Ulama’ (NU) organization. In the midst of the discriminatory issues against women and gender mainstreaming bias, NU consciously and courageously opens up to make space for an expanded discussion of the role of women even in the area of Islamic law (fiqh), which is considered sacredly. Not only in theoretical-normative, but also NU showed consistency in the implementation for the ideas of women roles in the public sphere significantly, although a number of issues is still on the agenda of feminist struggle in the Muslimah community, such as violence against women in the household (domestic violence) and gender mainstreaming issues in a variety of positions in the executive, legislative, and judicial branches of government as well as other strategic institutions. The certain thing is that the feminist movement in Indonesia showed a significant effect on the changes in the political, social, legal, and economical areas.